POTENSI HIPOGLIKEMIK EKSTRAK ETANOLIK DAUN SRIKAYA - Yance Anas; Kenyo Alexandra Oktaviani; Suharjono Suharjono (Universitas Wahid Hasyim Semarang, 2010)
ABSTRACT Active compounds in the leaves of sugar apple is believed to lower blood sugar levels, so it can be used as an oral hypoglycemic agent in the treatment of diabetes. The purpose of this research is to prove the hypoglycemic effect of ethanol extract of sugar apple leaves in Wistar male rats. The research was conducted by using oral glucose test in the group of rats who received treatment doses of sugar apple leaves etanolik extract (75.6, 151.2 and 302.4) mg / KgBW and control groups. Test materials were given 30 minutes before loading 2g/KgBB glucose orally. Research data is the blood glucose level every time which is converted into data AUC0-300 and % hypoglycemic effect. Potential hypoglycemic effects (ED50) were measured using probit analysis. Statistical analysis performed using Kruskal-Wallis test followed by Mann-Whitney test at the level of 95%. In addition, also identified the active compound flavonoid with qualitative chemical analysis method. The results showed that ethanol extract of leaves of sugar apple dose (75.6, 151.2 and 302.4) mg / kg has a hypoglycemic effect on male wistar rats subjected to glucose (P <0.05), with the percentage hipogllikemik effect amounts to (11.05, 23, 01 and 42.793)%. Potency (ED50) etanolik extract sugar apple leaves as hypoglycemic agents amounted to 339 mg / KgBW. In this study, ethanol extract of sugar apple leaves positive active compounds containing flavonoid. Key words: hypoglycemic, sugar apple